Language and the opportunity to learn science in bilingual classrooms in the Eastern Cape, South Africa - Probyn, Margaret Joan (School of Education, 2017)
The problem that prompted this research was the general poor performance of South African learners in national and international science assessments, and in particular, the poor achievement levels of Grade 8 learners in successive TIMSS (Trends in International Mathematics and Science Study) science assessments. It was suggested in the TIMSS South Africa reports that the language of the tests, when different to learners' home language, contributed to their poor performance in the assessments. However the reports also noted that language factors were intertwined with other factors such as low socio-economic status. Large-scale quantitative studies such as TIMSS can tell us the 'what' in an education system; however such studies are not able to tell us much about 'why': for example why South African learners have continued to perform so poorly in assessments such as TIMSS. The notion of 'opportunity to learn' proposes that learners cannot be held accountable for their performance in such assessments if they have not been provided with the opportunity to learn the content assessed. This small-scale qualitative research study therefore set out to drill down from the TIMSS studies to investigate the opportunity to learn science in classrooms in the Eastern Cape where the home language of learners and teachers (isiXhosa) was different to the language of assessment (English). Opportunity to learn science was conceptualized in terms of the science content of lesson and the language used to construct that science knowledge. Classroom language was further disaggregated into the classroom discourse interaction patterns; and the bilingual languaging practices of teachers and learners. The research thus drew on literature and research from the fields of science teaching, classroom discourse, and bilingual education - fields not usually combined - to develop a complex picture of classroom practices. A multiple case study was undertaken in eight township and rural schools in the Eastern Cape Province of South Africa, one of the most under-developed and poorest of the nine provinces. Data was collected from five consecutive Grade 8 science lessons that were observed and videotaped for each of eight classes; the teachers were interviewed about their personal histories, attitudes towards teaching and learning science in the context where learners were learning through an additional language; and their classroom practices. In addition, detailed fieldnotes were kept. Transcripts were made of the lessons and interviews; and the isiXhosa in the lessons was translated where it occurred. The lesson transcripts were analysed using socio-cultural discourse analysis and this included coding and content analysis to arrive at patterns in the data, which were exemplified by extracts from the data; some of these were of necessity fairly long, so as to take account of both the content and language of the lessons and to trace how ideas were developed over time, within and across lessons, though language. The teacher interviews provided the contextual detail; and teachers' practices were probed using simulated recall based on video clips from their lessons. The fine-grained analysis of the science content of lessons allowed for the elaboration of a hierarchy of necessary conditions that needed to be in place for the opportunity to learn science to be actualized; and a key condition was that the science content should be conceptually coherent, with facts linked to generalized principles and conceptual frameworks and that the generalized principles were supported by factual detail. It appeared that the classroom discourse was important for engaging learners in this process of moving from description of observations, to explanation, to generalizing and concept building. In addition a skilled teacher was able to effect a bridging discourse that supported learners in moving from everyday language and understandings to scientific language and understandings; from practical to theoretical knowledge; and from oral to written modes. These are necessary conditions for all learners to be afforded the opportunity to learn science. A further condition in the bilingual contexts that these classrooms typified, was the need for the teacher to support learners in developing conceptual understanding in their home language and then teaching for transfer of that understanding into the language of assessment, English. The analysis was able to demonstrate how the nuanced interplay of content and language in the practice of one teacher appeared to successfully construct the opportunity to learn science; and how in the practices of the other teachers, the opportunity to learn science broke down at different points. This indicated the points of leverage in the enacted curriculum that could be addressed in teacher education to break the logjam of factors contributing to underperformance in science achievement.